2022
DOI: 10.3390/jcm11061668
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Profiles in School-Aged Children with Autism Spectrum Disorder: A Descriptive Study Using the Sensory Processing Measure-2 (SPM-2)

Abstract: Background: Sensory reactivity is considered one of the diagnostic criteria for Autism Spectrum Disorders (ASD) and has been associated with poorer functional outcomes, behavioral difficulties, and autism severity across the lifespan. The characterization of the sensory processing in ASD has thus become crucial to identify the sensory and motor features influencing the development of personal autonomy. Objectives: The present study has two aims: (1) to compare the sensory processing between school-aged childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…Furthermore, tactile physical sensations (82.9%) and look “just-right” perceptions (75.6%) are more frequent in our ASD-group. Of note, atypicality in visual and tactile processing were frequently reported as a typical sensory difficulty in children with ASD ( 43 ). Certainly, it would be desirable to make a thorough assessment of SP in ASD, comparing USP-SPS with other tools evaluating abnormalities in sensory processing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tactile physical sensations (82.9%) and look “just-right” perceptions (75.6%) are more frequent in our ASD-group. Of note, atypicality in visual and tactile processing were frequently reported as a typical sensory difficulty in children with ASD ( 43 ). Certainly, it would be desirable to make a thorough assessment of SP in ASD, comparing USP-SPS with other tools evaluating abnormalities in sensory processing.…”
Section: Discussionmentioning
confidence: 99%
“…Another study among Saudi Arabian children, by Al-Heizan et al, reported similar results, with a higher prevalence of sensory dysfunction in children with ASD [ 21 ]. Other studies have pointed to the effect of such sensory difficulties on social communication [ 57 ], more severe restricted and repetitive behaviors [ 58 ], feeding [ 59 ], and sleep problems [ 60 ] in children with NDDs. The results of our current study indicate increased rates of motor difficulties in most children with NDDs, with 31% and 58% scoring below average and low in the motor skills domain, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Conners' Parent and Teacher Rating Scale‐Revised: short form (CPRS‐R:S and CTRS‐R:S) were used to assess inattention and hyperactivity problems and to rule out a possible ADHD comorbidity. Sensory processing difficulties, praxis and social participation were assessed using the Sensory Processing Measure (SPM) (Narzisi et al, 2022).…”
Section: Methodsmentioning
confidence: 99%